Grammatical errors in paragraph writing of first year English major students at School of Foreign Languages – Thai Nguyen University - Trần, Thị Hạnh (ĐHNN, 2017)
This paper studies common grammatical errors in paragraph writing committed by first year English major students at School of Foreign Languages – Thai Nguyen University (SFL - TNU) and the causes of these errors. To achieve the desired aims of current study, the author combined both qualitative and quantitative methods, including the instrument namely students’ writing analysis. The participants in the research were fifty first year English major students at SFL - TNU. Research results show that first year English major students at SFL - TNU often commit errors in sentence structure, verb usage, preposition usage and singular/plural nouns. Besides, the main causes of these errors are mother tongue interference, overgeneralization, ignorance of rule restrictions, incomplete application of rules and false concepts hypothesized; in which interference of native language and overgeneralization are the most common ones. In order to minimize these errors, it is suggested that teachers help students practice writing and correct their writings effectively by suitable and flexible techniques